(untitled) (Research, Society and Development, 2022)
This article aims to establish the epidemiological profile of women victims of sexual violence attended in a center specialized in infectious-parasitic diseases of Cascavel/PR. To accomplish this objective, an exploratory and descriptive, retrospective, cross-sectional study was carried out through the analysis of medical records of patient’s victims of sexual violence, from April 2018 to December 2019, in the municipality of Cascavel/Paraná. The medical records were made available by the Health Department of Cascavel/PR. The sample consisted of 69 cases of women, of all ages, who suffered proven sexual violence through medical records, attended at the Center for Infectious-Parasitic Diseases (CEDIP). The criteria analyzed were: age group, self-declared color, schooling, if a police report, marital status, occupation, sexual orientation, if there was a repetition of violence, means used to effect violence, type of abuse, number of aggressors, physical conditions of the victim, HIV prophylaxis, STIs and contraception, reactive tests, post-violence pregnancy, aggressor’s sex, age group of the aggressor and degree of knowledge of the aggressor. The data found were analyzed using the Microsoft ® Excel® 365.V16, organized, tabulated and transformed in tables and graphs. After that, content analysis and association were made with the texts presented in the theoretical framework. Through the knowledge generated by this research, it is possible to establish preventive actions to abuse, which address the reality of the population studied, in addition to establishing primary care actions in the specialized center.